An assessment of functional limitations and its relation to morbidity pattern among the elderly residing in urban area, Kerala, India - Pillai, Arshia S.; Francis, Paul T.; Kartha, Niveditha; Mathew, Minu Maria (International Journal Of Community Medicine And Public Health, 2021)
Background: Ageing is an inevitable process and a person aged 60 years or above is often referred to as ‘elderly’. Older age is characterized by emergence of several complex health states that tend to occur only later in life and that do not fall into discrete disease categories. These are commonly called as geriatric syndromes. The aim of the study was to estimate the prevalence of functional limitations among the elderly and to determine the association between functional limitations and morbidity pattern among the elderly residing in urban area in Ernakulam district, Kerala. Methods: A community-based cross-sectional study was carried out among 302 elderly participants by using cluster sampling technique in two urban areas of Ernakulam. The structured questionnaire included socio-demographic details, diagnosed morbidities and modified Barthel index to assess functional limitations. Results: The overall prevalence of functional limitations was 22.4% among the elderly. Functional limitations were significantly associated with acid peptic diseases, constipation, kidney disorder, urinary tract infection, arthritis/joint pain, visual impairment, senile deafness and edentulous mouth. Conclusions: In our study 22.4% of the elderly had some form of functional limitations in terms of difficulties in performing basic ADL. Association of functional limitations and different type of morbidities were found in acid peptic diseases, constipation, kidney disorder, urinary tract infection, arthritis/joint pain, visual impairment, senile deafness showed statistically significant. Individuals who had edentulous mouth was also found to be statistically significant.